PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KINERJA KEUANGAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAN MANUFAKTUR YANG TERDAFTAR DI (BEI) PERIODE 2017-2019 - Ahmad, Ardian; Rasyid, Ardiansyah (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to empirically examine the effect of managerial ownership, institutional ownership, financial performance, and company growth on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This study uses 44 manufacturing companies as a sample and uses multiple regression analysis. The results of this study indicate that managerial ownership does not have a significant positive effect on dividend policy, institutional ownership does not have a significant positive effect on dividend policy, financial performance does not have a significant positive effect on dividend policy, and company growth has a significant positive effect on dividend policy.